The Effect of Sodium Gluconate on Pastes’ Performance and Hydration Behavior of Ordinary Portland Cement - Xingdong Lv; Jiazheng Li; Chao Lu; Zhanao Liu; Yaosheng Tan; Chunfeng Liu; Beixing Li; Rongkai Wang (Advances in Materials Science and Engineering)
The goal of this paper provides better understanding of the effect of sodium gluconate (SG) on ordinary Portland cement (OPC) hydration behavior. Pastes’ performances of ordinary Portland cement, including setting time at 20°C and 35°C curing temperature, mechanical strength, fluidity, and zeta potential are studied. Furthermore, the effects of SG on cement hydration behaviors are investigated by the means of isothermal calorimetry measurements, X-ray diffraction (XRD), and thermogravimetric analysis (TGA). The results show that SG is difficult to maintain significant retarding effect at the temperature of 35°C compared to that at the temperature of 20°C. SG is able to reduce the cement cumulative hydration heat and delay the occurrence time of heat evolution peak in a certain extent, but it has little impact on reducing the cement evolution rate peak. The effects of SG on mechanical properties and dispersion properties of cement depend on its dosages. Specifically, the positive effect occurs when the addition dosage is less than 0.15% (i.e., by cement weight), but the negative effect emerges if the addition dosages exceed this limitation. Similarly, SG plays different roles on cement hydration at different hydration periods. It inhibits the hydration of C3S and the formation of portlandite (CH) at the early hydration period. On the contrary, it promotes the C3S hydration when hydration time is beyond 1 d. Meanwhile, SG also plays different roles on cement hydration at different dosage additions. Specifically, SG promotes ettringite (AFt) formation at the dosage less than 0.06%, but it inhibits AFt formation at the dosage more than 0.06%.